Determination of Organic and Inorganic Components of Commercial Chicken Eggshell Obtained From Sebha Local Market-Libya - Salma B. Kalifah (Journal of Pure & Applied Sciences, 2019)
An experimental study has been carried out aiming to identify the composition of eggshells of chicken eggs obtained from Sebha markets during March 2016. The selected chicken eggshells were washed, dried, and grinded to a powder. The results obtained showed that the tested chicken eggshells samples contain [0.6±0.24%] moisture, [99.75±0.02%] dry matter, [2.57±0.10%] protein, [4.7±0.1%] fiber, [1.97±0.24%] Carbohydrate and [90.75±0.21%] ash. The mineral elements contained in the selected chicken eggshells samples have been identified and the results obtained showed different amounts as [mg / 100g] of dry weight [Ca 2+ =2442.6, Mg 2+ =134.8, Cu 2+ =12.12, Na + =4.97, K + =5.21, Fe 2+ =5.61, Mn2+ =0.36, Cd2+ =0.74 and Zn2+ =1.69], Pb2+ was not detected. As a result, the amounts of minerals detected showed that this type of tested chicken eggshells are of good quality and can be further utilized for different purposes.